If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2 + -1y) = 0 Remove parenthesis around (2 + -1y) 2 + -1y = 0 Solving 2 + -1y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -1y = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -1y = 0 + -2 -1y = 0 + -2 Combine like terms: 0 + -2 = -2 -1y = -2 Divide each side by '-1'. y = 2 Simplifying y = 2
| 0=-2x^2+40x+5 | | 17.5+4x=6.5(3x-6) | | 8y-5=3(2-y) | | 6x/5•1/4x | | -6x-3x+12x-4=-1 | | 9n+12=15n-6 | | 8=e/-7 | | 9x-96=6x-9 | | 2/3x^-1/3=0 | | an-7an-1+10an-2=4n | | (2k^2-4k+5)=0 | | 1y+3-1y=3 | | -3+6-3x+7x=14 | | ln*lnx/2-lnx0 | | 10m=-36+86 | | 3r-72=25 | | -13y=-13 | | 15=5/3x-10 | | 1y+12-1y=3 | | 95-2x=16x+19 | | 18-2(-4+2)= | | 6x-3x+7=-3 | | z^8=2 | | 7(8+6p)=392 | | 3x^3+9x^2-120x=0 | | z^5=-2i | | 84=7(-4p+8) | | 10x^4-1=0 | | 5550000x+2085000000=3056890000-15000000x | | -3.5x+4.2=1.9x-2.7 | | 7(2-2p)=-98 | | 224=-8(7p-7) |